Myocardial Contractile Dysfunction Is Present without Histopathology in a Mouse Model of Limb-Girdle Muscular Dystrophy-2F and Is Prevented after Claudin-5 Virotherapy - Milani-Nejad, Nima; Schultz, Eric J.; Slabaugh, Jessica L.; Janssen, Paul M. L.; Rafael-Fortney, Jill A. (Frontiers in Physiology, 2016)
Abstract Mutations in several members of the dystrophin glycoprotein complex lead to skeletal and cardiomyopathies. Cardiac care for these muscular dystrophies consists of management of symptoms with standard heart medications after detection of reduced whole heart function. Recent evidence from both Duchenne muscular dystrophy patients and animal models suggests that myocardial dysfunction is present before myocardial damage or deficiencies in whole heart function, and that treatment prior to heart failure symptoms may be beneficial. To determine whether this same early myocardial dysfunction is present in other muscular dystrophy cardiomyopathies, we conducted a physiological assessment of cardiac function at the tissue level in the δ-sarcoglycan null mouse model (Sgcd-/-) of Limb-girdle muscular dystrophy type 2F. Baseline cardiac contractile force measurements using ex vivo intact linear muscle preparations, were severely depressed in these mice without the presence of histopathology. Virotherapy with claudin-5 prevents the onset of cardiomyopathy in another muscular dystrophy model. After virotherapy with claudin-5, the cardiac contractile force deficits in Sgcd-/- mice are no longer significant. These studies suggest that screening Limb-girdle muscular dystrophy patients using methods that detect earlier functional changes may provide a longer therapeutic window for cardiac care.